Kontribusi Hutan Rakyat terhadap Ketahanan Pangan Rumah Tangga Petani Kecamatan Rumpin, Kabupaten Bogor - Siti Nur Indah Lestari; Hardjanto Hardjanto; Yulius Hero (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2018)
Private forest is one of the alternatives to support food security and household income. The research is located in village of Cidokom, Leuwibatu, and Mekarjaya, Subdistrict of Rumpin with 66 respondents. This study aims to analysis contribution of private forest to the total household income and food security of farmer households Data was collected by field observation, interview and literature study. Analysis of contribution to food security was done by calculating total energy from all crop production with unit of cap/cal/day by comparing the recommended daily consumption of energy and nutritional value (AKG) of 2150 kcal/person/day. The level of household food security is measured by using food share. Food share is cross-classification of two indicators of food security. The two indicators are the share of food expenditure and the adequacy of energy consumption (kcal). The results showed that (1) The average contribution of private forest for household income from timber plantation is 10.63% and food crops is 30.22% of total income, (2) there are 46 types of crops which contribute to food security per day with average 393.70 cal/cap/day or 18.75% from total energy/day/person,(3) the distribution of households that have food resistant (TKE>90%) is 69,69%.KeyWords: Private forest, agroforestry, food security